A Tomato Sorting Automation Prototype Based on Color: Prototype Otomasi Penyortir Buah Tomat Berdasarkan Warna - Zain, Abdul; Zainal, Isradi; Tungga, Rifaldy Atlant (Politeknik Negeri Ujung Pandang, 2024)
Abstract—The process of sorting tomatoes can be done using visual methods by paying attention to color. The purpose of this research is to improve the process of sorting tomatoes based on color in distinguishing ripe tomatoes and immature tomatoes. Streamline the time of sorting tomato fruit in order to avoid losses due to spoilage. This research method is with a sample of tomato fruit taken RGB value through TCS 3200 color sensor according to the level of maturity. After the RGB value is obtained, it will be processed into the Arduino Uno to obtain maturity information through the rules that have been made and sorted using a servo motor. The results of this study indicate that a good condition for detecting tomato fruit is with a closer distance to the fruit with a dark background. This is because there is no excess light reflection so that the TCS sensor can take RGB values well and reduce the occurrence of misreading of ripeness information in the sorting process. Keywords— Tomato, Sensor TCS 3200, Arduino uno, Motor Servo.